gem-Difluorovinyl and trifluorovinyl Michael acceptors in the synthesis of α,β-unsaturated fluorinated and nonfluorinated amides - Bilska-Markowska, Monika; Kaźmierczak, Marcin; Jankowski, Wojciech; Hoffmann, Marcin (Beilstein Journal of Organic Chemistry, 2024)
The incorporation of fluorine atoms within the structure of organic compounds is known to exert a significant impact on their electronic properties, thereby modulating their reactivity in diverse chemical transformations. In the context of our investigation, we observed a striking illustration of this phenomenon. A Michael addition involving gem-difluorovinyl and trifluorovinyl acceptors was successfully achieved, demonstrating high stereoselectivity. This selectivity was further elucidated through theoretical calculations. Using this methodology, a series of new α,β-unsaturated amides, both fluorinated and nonfluorinated, were synthesized.
Keywords: gem-difluorovinyl Michael acceptors; Michael addition; trifluorovinyl Michael acceptors; α,β-unsaturated amides